Labor insertion of youth: the context and their opinion about work definitions - Thomé, Luciana Dutra; Telmo, Alice Queiroz; Koller, Silvia Helena (Paidéia (Ribeirão Preto), 2010)
The aim of the study was to investigate the context of labor insertion of youth workers and non-workers and their opinion about work definitions. There were 7425 participants, aged between 14 and 24 years old, both genders, of low economic level. The instrument was a questionnaire about risk and protective factors. The data analysis included descriptive statistics, chi-square and Student t test. Some results showed youth workers find more opportunities of informal work and receive remuneration lower then a minimum wage, considering that they work between 5 and 8 hours a day. In the total sample, the meanings of work as "useful production of something" and "money" were distinguished. These dimensions can reflect the search for a constructive and productive work for the individual and society, that provides survival conditions for them and their family. Youth lacks of a formal work, with benefits and perspective of professional ascension.